Influence of the Radial Clearance on the Center Orbit of the 5S-FE Engine's Connecting-Rod Big End Bearing - Nguyen, Dinh Tan; Tran, Thi Thanh Hai; Luu, Trong Thuan (Old Journal, 2018)
The connecting-rod big end bearing is the connecting part between the connecting-rod and the crankshaft, subject to varying loads according to the operation cycle of the engine. Therefore, the lubrication characteristics of the connecting-rod big end bearing vary according to the operation cycle of the engine. Eccentricity between the journal center and center of the connecting-rod (housing bearing) is one of the important lubricating properties that directly affect the oil film thickness. The article presents a numerical simulation the journal's center orbit of 5S-FE engine's connecting-rod big end bearing when changing the radial clearance base on the solving of the modified Reynolds equation in the hydrodynamic regime and equilibrium of the charge equation by the finite element method. Simulation results were compared with the results from the ACCEL software (the software is developed by the University of Poitiers' in France for car manufacturing to solve the problem of connecting rod lubrication).